Application of rps16 Intron and trnL-trnF Intergenic Spacer Sequences to Identify Rengas Clone Riau - Roslim, Dewi Indriyani; Herman, Herman (Biosaintifika: Journal of Biology & Biology Education, 2017)
Rengas clone Riau has been identified using morphological characters and molecular technique with a psbA-trnH intergenic spacer, however, this method can only determine its taxonomic status at genus level, namely Gluta sp. This study reports application two DNA barcodes, i.e. rps16 intron and trnL-trnF intergenic spacer, to identify Rengas clone Riau. The methods included collection of the leaves from Kajuik Lake, total DNA isolation, electrophoresis, PCR (polymerase chain reaction), gel purification and sequencing. The rps16 intron size was 659 bp and the trnL-trnF intergenic spacer was 527 bp. The BLASTn analysis showed that sequences of the rps16 intron and the trnL-trnF intergenic spacer of Gluta sp clone Riau had 100% similarity to those of G. renghas deposited in GenBank. These results were supported by high max score, high total score, query cover = 100%, and E-value = 0. The dendrograms also showed the closest relationship of Gluta sp clone Riau with G. renghas deposited in GenBank compared to other species of Gluta. In conclusion, this study succeeded in identifying Rengas clone Riau as Gluta renghas by using sequences of the rps16 intron and the trnL-trnF intergenic spacer. A combination of DNA barcodes could be applied to identify various plants as long as the database for the DNA barcodes is available in public database such as GenBank.